Association between forced expiratory volume and waist-hip ratio in school with overweight and obesity - Etges Schuster, Vanessa (2024)
Objective: To evaluate the association between forced expiratory volume in the first second (FEV1) and waist-to-hip ratio (WHR) in overweightand obese students. Method: A cross-sectional study was conducted to evaluate children and adolescents of both sexes (7 to 17 years old) classified according to body mass index (BMI) in the eutrophic (EG), overweight (OWG), and obesity group (OG). The WHR and pulmonary volumes were evaluated using digital spirometry. Result: Sample (N=320) with an average age of 11.51 ± 2.74 years (EG [n=140]; OWG [n=88]; OG [n=92], with WHR of 0.78 [0.73 – 0.82] cm, 0.80 [0.76 – 0.83] cm, and 0.85 [0.80-0.89] cm, respectively. There was a significant difference in FEV1 between OG (2.20 L) and EG (2.71 L) (p= 0.037), with WHR varying between EG (0.78 cm) and OG (0.85 cm) (p<0.001) and between OWG (0.80 cm) and OG (0.85) (p<0.001). There was a significant, inverse, and moderate correlation between WHR and FEV1 in the EG (p<0.001, r= -0.448) and OWG (p<0.001, r= -0.421) whereas in the OG, there was a significant, inverse, and weak correlation (p<0.002, r=-0.325). Conclusion: FEV1 was inversely associated with WHR, indicating that excess body weight affects lung function.